Spatio-Temporal Analysis of Thermal Comfort in High-Density Residential Areas in the Urban Region of Unaaha - Khudrin, Khudrin; Nurgiantoro, Nurgiantoro; Hidayat, Ahmad; Jaya, Laode Muhammad Golok; Herman, Boi; Kumar, Shivneel (Sustainability (STPP) Theory, Practice and Policy, 2025)
Thermal comfort plays a vital role in the health, productivity, and well-being of urban communities and serves as a critical indicator in sustainable urban planning. This study aims to analyze thermal comfort levels in dense residential areas and planned residential zones within the Unaaha urban area, using satellite data from two specific years, 2014 and 2024, selected to capture a decade of urban change. The methodology employs Landsat 8 OLI/TIRS imagery complemented by shapefile data of planned residential areas in Unaaha District, providing spatial context for detailed analysis. The spatial resolution and quality of the satellite imagery ensure reliable detection of land surface temperature and vegetation changes. A series of index transformations, including Urban Index (UI), Normalized Difference Vegetation Index (NDVI), Normalized Difference Moisture Index (NDMI), Land Surface Temperature (LST), Modified Temperature Humidity Index (MTHI), and Thermal Index (TI), were applied to assess thermal comfort dynamics. Results indicate significant changes in thermal comfort between 2014 and 2024, with a shift in dominant categories from “uncomfortable” (60.5%) in 2014 to “less comfortable” (67.71%) in 2024 within dense residential areas. Evaluation of the 2024 planned residential zones reveals a predominance of “less comfortable” (45.34%) and “uncomfortable” (27.81%) classes. These findings suggest that current residential planning has not adequately balanced green open spaces and built-up areas, thereby limiting the natural cooling effects. This outcome aligns with previous studies emphasizing the critical role of green infrastructure in mitigating urban heat, underscoring the need for integrative planning approaches that prioritize thermal comfort in urban development.